Challenge of the Magi - Smith, Mark, author 562384; Thomson, Jamie, 1958-, author 562386; Davis, Jon, illustrator 563399 (London : Armada, 1986)
Similar in some regards to the Ace of Aces book series, Duel Master takes 2 players, each with their own book, into competition with one another. Play is paragraph based, with each player making their own choices about what they want their character to do. In "The Challenge of the Magi", each player takes on the role of a mage (specializing in one of five types or colors of magic), putting themselves forward as replacement for the recently deceased head of the council. Who shall rule is determined by ritual duel to the death in the Rainbow Land - a series of interconnected dimensions, each filled with its own denizens and incorporating its own magical laws.